Problems of interstate dialogue of the people's Republic of China – Republic of Kazakhstan in the domestic and foreign historiography. - Batpenova., Z. S.; Suleimenova., M. M. (Journal of Oriental Studies, 2016)
The importance of foreign policy interaction of China and Kazakhstan found reflection in works of experts in international policy – political scientists, economists, historians. The considerable emphasis is placed on problems of the interstate relations of the PRC-PK owing to intensive and continuous cooperation of the countries. Both in domestic and in foreign historiography questions of bilateral cooperation are considered not in complex researches, but separate aspects of the interstate relations are affected.